Dramaturgi Pemilihan Presiden Indonesia 2014 - Arif, Farida M. (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
Political campaign aims to achieve a particular change, including changes in attitudes and behavior of a large number of individuals. Indonesian presidential election in 2014, candidates utilizing mass media andshow a good image of him. Imaging is considered an effective way of campaign to persuade the public to vote. Imaging is performed by the presidential candidates in accordance with the dramaturgical concept introduced by Erving Goffman. The observation states that both candidates are equally display his front stage as possible so that people know them as a potential leader firm or simple. Where it also affects the sound acquisitioncandidates.